PENGARUH BAHAN AJAR INTERAKTIF TERHADAP HASIL BELAJAR SEJARAH SISWA SMA DI PADANG PANJANG : APLIKASI COURSE LAB 2.4 - Yosi Oktaviana; Wahidul Basri; Aisiah Aisiah (PAKAR Pendidikan, 2019)
This study aims to look at the effect of using interactive course lab teaching materials on students' ability to understand concepts in historysubject. The problem of this study is the low level of students' knowledge of the concept material which is indicated by the low learning outcomes of IPS X grade students of high school in Padang Panjang are still many under the KKM (75). The teacher still does not use interactive teaching materials in learning. For this reason, we need an interactive teaching material that has not been used in Padang Panjang High School which is expected to improve learning outcomes. In connection with that Alvani Maizal Asri (2018) has made an interactive teaching material in his research entitled "Development of interactive teaching materials using the course lab application on Indonesian History subjects. The solutions offered in this study introduce the use of interactive teaching materials in historical learning and also as a follow-up to Alvani Maizal Asri's research to continue the next phase of Development. This type of research is experimental research. The population of this study was class X IPS with a sample of 181 people taken by random sampling. Data retrieval is done by pretest and posttest by using multiple choice questions as many as 40 questions. Data analysis using normality test, homogeneity test and hypothesis test (t test) and effectiveness test. The findings of the study at SMAN 1 Padang Panjang showed the average value of the difference between the experimental class students' learning outcomes 11,14 and SD 2,75 while the average difference in learning outcomes of the control class students was 10.14 with SD 2.25. Analysis of the normality test showed that the two samples were normally distributed, namely Lhit <Ltab which was 0.814 <0.886. The omogenicity test results show that the smapel has a homogeneous variant, the Fhit was 1.58 <Ftab was 1.701. The results of the t test show Thit 3.96> Ttab 2.05 so that it can be stated H1 is accepted H0 is rejected. While the results of research at SMAN 2 Padang Panjang showed the average value of the difference in learning outcomes of experimental class 12 students with SD 3.03 while the average difference in learning outcomes of control class students was 10.7 with SD 2.54. Analysis of the normality test showed that the two samples were normally distributed, namely Lhit <Ltab which was 0.821 <0.886. The omogenicity test results showed that the sample had a homogeneous variant, namely Fhit 1.58 <Ftab 1.69. The results of the t test show Thit 2.197> Ttab 2.03 so that it can be declared H1 accepted H0 rejected The results of the study show that there is an influence of the use of interactive teaching materials on the results of history learning of high school students in Padang Panjang. This interactive teaching material is effective to use because the average N-gain value at SMAN 1 Padang Panjang is 0.42 with moderate criteria, as well as in SMAN 2 Padang Panjang, the average N-gain value is 0.33 with the medium category.